The joy of the snow - Goudge, Elizabeth (Coward, McCann, & Geoghegan, Inc. New York, 1974)
Here is the book eavery reader - and their name is legion - of Elizabeth Goudge's wonderful novels has always wanted: the story of Miss Goudge's own life and the background to her writing. Four decades and more than twelve million copies after her American debut, the author of The Child from the Sea, Green Dolphin Street, and The Scent of Water has written an enduring, personal, and inspiring account of her own progress from a sheltered childhood to international acclaim.
Includes index.
Keywords: Goudge, Elizabeth -- 1900-1984.; Novelists, English -- 20th century